Aplikasi Mobile untuk Usaha Jasa Pengantaran Barang di Dusun Cibeber, Kawasan Industri Jababeka, Bekasi - Tjong Wan Sen (President University, 2019)
This Community Services Activity is meant to provide alternative income sources for citizens in Dusun Cibeber which is located in the center of Jababeka Industrial Estate, Cikarang, Bekasi. In this activity advancement of computer and information technology, global positioning system, and telecommunication networks are used to produce a mobile application for delivery services that is easy to use, low cost, and could be operated by common person. The application together with its supporting components has already successfully developed, implemented, and simulated. Next phase would be to measure its performance widely in the real environment.